Layered intramagmatic dike in the anortosite intrusion on the Berthelot Islands (Argentine Islands archipelago, West Antarctica) - G.V. Artemenko; V.G. Bakhmutov; I.A. Samborskaya; L.N. Bakhmutova (Ukrainian Antarctic Journal, 2015)
The observed layering of the intramagmatic dike of basic composition on the Berthelot Island is probably determined due to the impregnation of partially solidified magma in the fracture into the cooling anorthosite intrusion. The melt of dikes was enriched on V, Cr, Сu, P and Sc, which indicate their late magmatic nature. The intramagmatic dike in the gabbro intrusions on Petermann Island and Cape Tuxen have the significant differences in chemical composition, which is probably determined by the different composition of the original magma. They shown of ore - V, Co, Cu and Zn mineralization. The results of geochemical studies of ore enriched magmatic phases of solidifying cooling gabbro intrusions are predict the ore content of gabbroid intrusions of the Andean complex.